2021
DOI: 10.14334/wartazoa.v31i1.2530
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin Gene as a Genetic Marker for Growth and Carcass Traits in Beef Cattle

Abstract: <p>Growth and carcass traits are of economic importances in livestock breeding, because they affect the profitability of animal production. The phenotypic expression of these traits is controlled by multiple genes (polygenes), such as myostatin (MSTN) gene. This paper aims to discuss the expression, polymorphism and potential application of MSTN gene as a marker-assisted selection (MAS) for growth and carcass traits in beef cattle based on data from published studies. MSTN gene or known as growth and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Considering the importance of this gene, investigation of the biological roles of the MSTN gene in Ongole cattle is required because mutations in some of the other beef cattle, including European cattle [ 23 , 27 , 28 ], Australian breeds [ 30 ], and Indonesian beef cattle [ 31 , 32 , 35 ] are associated with growth traits. The literature search revealed that there is no prior research examining the allelic and genotypic frequencies of the MSTN gene in SO cattle, making direct comparisons with other studies in Ongole cow breeds worldwide difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance of this gene, investigation of the biological roles of the MSTN gene in Ongole cattle is required because mutations in some of the other beef cattle, including European cattle [ 23 , 27 , 28 ], Australian breeds [ 30 ], and Indonesian beef cattle [ 31 , 32 , 35 ] are associated with growth traits. The literature search revealed that there is no prior research examining the allelic and genotypic frequencies of the MSTN gene in SO cattle, making direct comparisons with other studies in Ongole cow breeds worldwide difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the MSTN gene in economic production has been identified in various breeds of beef cattle, such as Belgian blue [ 26 ], Nellore cattle [ 25 , 27 ], Piemontese young bulls [ 23 , 28 ], Russian cattle [ 2 ], Marchigiana bulls [ 3 ], and, Chinese yellow cattle [ 29 ]. The trait can be found in Australian beef cattle [ 30 ] and in some breeds of Indonesian beef cattle, such as the Peranakan Ongole (PO), the Belgian Blue × PO hybrid, and the PO × Pegolo Bali cattle [ 31 , 32 ]. However, the result might probably be different from other Ongole beef cattle extensively grazed under a harsh environment in a tropical semi-arid region, such as Sumba Island [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Karakterisasi gen MSTN akan sangat bermanfaat bagi beberapa cattle di Indonesia (Prihandini et al, 2021). Namun, karakterisasi ini belum sepenuhnya dilakukan.…”
Section: Dengan Menggunakan Sekuens Dari Ncbi Pada Spesiesunclassified
“…Improving meat quality: Meat from buffalo is highly valued in Indonesia. Genetic selection can help identify animals with desirable meat quality traits, such as marbling, tenderness, and flavor, improving the value and marketability of buffalo meat [91,92]. Data management systems and software applications can support the genetic improvement of buffaloes at BPTU-HPT.…”
Section: Opportunities For Genetic Improvementmentioning
confidence: 99%